"The value of pre‐ and co‐seasonal sublingual immunotherapy in pollen‐induced allergic rhinoconjunctivitis". Issue 1 (4th May 2015) - Demoly, Pascal; Calderon, Moises A; Casale, Thomas B; Malling, Hans‐Jørgen; Wahn, Ulrich
Abstract: Allergen immunotherapy (AIT) is a guidelines‐approved, disease‐modifying treatment option for respiratory allergies, including allergic rhinitis (AR) induced by pollen. The various AIT regimens employed to date in pollen‐induced AR can be classified as continuous (i.e. year‐round) or discontinuous (i.e. pre‐seasonal alone, co‐seasonal alone or pre‐ and co‐seasonal). Pre‐and co‐seasonal regimens are typically used for sublingual allergen immunotherapy (SLIT) and have economic and compliance advantages over perennial (year‐round) regimens. However, these advantages must not come at the expensive of poor efficacy or safety. The results of recent double‐blind, placebo‐controlled, randomized clinical trials show that pre‐ and co‐seasonal SLIT is safe and effective in patients with AR induced by grass pollen (treated with a tablet formulation) or by birch pollen (treated with a liquid formulation). Progress in SLIT has been made in defining the optimal dose of major allergen, the administration frequency (daily), the duration of pre‐seasonal treatment (four months) and the number of treatment seasons (at least three). Post‐marketing, "real‐life" trials of pre‐ and co‐seasonal birch or grass pollen SLIT regimens have confirmed the efficacy and safety observed in the clinical trials. In the treatment of pollen‐induced AR, pre‐ and co‐seasonal SLIT regimens appear to be at least as effective and safe as perennial SLIT regimens, and are associated with lower costs and good compliance. Good compliance may mean that pre‐ and co‐seasonal SLIT regimens are inherently more effective and safer than perennial SLIT regimens. When considering the pre‐ and co‐seasonal discontinuous regimen in particular, a 300 IR five‐grass‐pollen formulation is the only SLIT tablet with a clinical development programme having provided evidence of short‐term, sustained and post‐treatment efficacy.